2018
DOI: 10.1007/s13193-018-0741-y
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Wound Complications Following Extralevator Abdominoperineal Excision: Experience of a Regional Cancer Center

Abstract: Extralevator abdominoperineal excision (ELAPE) results in a large perineal defect which needs reconstruction by a flap or biological mesh. The incidence of perineal wound complications is thought to be higher following an ELAPE compared to conventional abdominoperineal excision (APE). WE aimed to analyze the perineal wound complications following ELAPE in our institution. This was a retrospective analysis of all consecutive patients who underwent an APE (conventional and ELAPE) procedure in our institution bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This multicenter case series suggests that minimally invasive TpAPE is feasible with acceptable intraoperative complications, no short-term mortality and a 9% severe postoperative complication rate within 30 days. The postoperative major morbidity rate of 9% compares favorably to major morbidity rates between 10 and 30% and perineal wound infection ranging from 11 up to 50% reported in large series and meta-analysis, but the current study is limited by the small sample size and inherent case selection bias [21][22][23][24][25][26]. Five intraoperative complications were reported, four of which were related to wrong plane surgery with sequential perforation, urethral, and pelvic sidewall injury.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This multicenter case series suggests that minimally invasive TpAPE is feasible with acceptable intraoperative complications, no short-term mortality and a 9% severe postoperative complication rate within 30 days. The postoperative major morbidity rate of 9% compares favorably to major morbidity rates between 10 and 30% and perineal wound infection ranging from 11 up to 50% reported in large series and meta-analysis, but the current study is limited by the small sample size and inherent case selection bias [21][22][23][24][25][26]. Five intraoperative complications were reported, four of which were related to wrong plane surgery with sequential perforation, urethral, and pelvic sidewall injury.…”
Section: Discussionmentioning
confidence: 58%
“…The postoperative major morbidity rate of 9% compares favorably to major morbidity rates between 10 and 30% and perineal wound infection ranging from 11 up to 50% reported in large series and meta-analysis, but the current study is limited by the small sample size and inherent case selection bias [ 21 26 ]. Five intraoperative complications were reported, four of which were related to wrong plane surgery with sequential perforation, urethral, and pelvic sidewall injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 7 It had been reported that the perineal wound complications were increased (range from 20% to 38%) after ELAPE. 8 , 9 A latest study reported that the rates of SSI after ELAPE was 26.3%. 10 In addition, preoperative radiotherapy and/or chemotherapy are often required for patients with low rectal cancer, which may also affect the healing of the surgical incision and increase the risk of SSI to approximately 31%.…”
Section: Introductionmentioning
confidence: 99%
“…However, laparoscopic surgery or open surgery in patients with rectal cancer after total mesorectal excision leaves a huge gap in the pelvic cavity. When the residual pelvic oor peritoneum is not suture, the small intestine will inevitably fall into the pelvic oor, causing the small intestine adhesion and increased the risk of intestinal obstruction [3]. Meanwhile, with increased intra-abdominal pressure and abdominal contents falling into the pelvic cavity, pelvic oor peritoneal hernia and delayed pelvic oor peritoneal healing will occur [4].…”
Section: Introductionmentioning
confidence: 99%